2022
DOI: 10.1073/pnas.2122477119
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose ethanol intoxication causes acute and lasting neuronal changes in the brain

Abstract: Alcohol intoxication at early ages is a risk factor for the development of addictive behavior. To uncover neuronal molecular correlates of acute ethanol intoxication, we used stable-isotope–labeled mice combined with quantitative mass spectrometry to screen more than 2,000 hippocampal proteins, of which 72 changed synaptic abundance up to twofold after ethanol exposure. Among those were mitochondrial proteins and proteins important for neuronal morphology, including MAP6 and ankyrin-G. Based on these candidate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 125 publications
0
14
0
Order By: Relevance
“…In contrast, our brief alcohol abstinence model may shed light, but it remains insufficient to conclude at this stage it is directly associated with accelerated cognitive and memory decline in the later stage of life. Nonetheless, a recent study, however, proposes this could potentially be the case as it is suggested that even a single dose of ethanol intoxication could lead to acute but also lasting neuronal and synaptic changes in the brain (Knabbe et al, 2022 ). Future in vivo studies are warranted with longer treatment and observation periods in older mice to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our brief alcohol abstinence model may shed light, but it remains insufficient to conclude at this stage it is directly associated with accelerated cognitive and memory decline in the later stage of life. Nonetheless, a recent study, however, proposes this could potentially be the case as it is suggested that even a single dose of ethanol intoxication could lead to acute but also lasting neuronal and synaptic changes in the brain (Knabbe et al, 2022 ). Future in vivo studies are warranted with longer treatment and observation periods in older mice to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses involve assumptions in addition to measurements and are of necessity more speculative. Mitochondria movement is known to affect synapse plasticity [Sun et al, 2013] [Vaccaro et al, 2017] [Knabbe et al, 2022]. It is possible we are seeing this effect in our data.…”
Section: Resultsmentioning
confidence: 66%
“…Mitochondria movement is known to affect synapse plasticity [Sun et al, 2013] [Vaccaro et al, 2017] [Knabbe et al, 2022. It is possible we are seeing this effect in our data.…”
Section: Time History Of Mitochondriamentioning
confidence: 59%
“…A study in Proceedings of the National Academy of Sciences recently reported that a single-dose exposure to ethanol in young adolescent mice 'causes acute and lasting neuronal changes in the brain… induces plastic changes which in turn could contribute to the basis of ethanol dependence'. 4 Adolescent alcohol exposure may also lead to changes in gene expression that could influence drinking behaviour in adulthood. 5 Even at low levels of consumption, alcohol intake in adolescence, a stage when breast tissue is most susceptible to neoplastic transformation, may increase later risks of breast cancer.…”
Section: Neuroadaptations Neoplastic Transformationsmentioning
confidence: 99%
“…Also, the mechanisms are becoming clearer: preclinical research suggests that introducing children and adolescents to alcohol may sensitise the neurocircuitry of addiction by inducing neuroadaptations in brain regions involved in reward and addiction. A study in Proceedings of the National Academy of Sciences recently reported that a single-dose exposure to ethanol in young adolescent mice ‘causes acute and lasting neuronal changes in the brain… induces plastic changes which in turn could contribute to the basis of ethanol dependence’ 4. Adolescent alcohol exposure may also lead to changes in gene expression that could influence drinking behaviour in adulthood 5…”
Section: Neuroadaptations Neoplastic Transformationsmentioning
confidence: 99%